The impact of the arts in healthcare on patients and service users: A critical review. (20th September 2017) - Boyce, Melanie; Bungay, Hilary; Munn‐Giddings, Carol; Wilson, Ceri
Abstract: This review provides an updated evaluation of the emerging body of literature on the value of the arts in healthcare settings. Internationally, there is growing interest in the use of the arts in the healthcare context supported by the number of research studies reported in the nursing and medical literature. There is evidence that arts interventions have positive effects on psychological and physiological outcomes on patients in a hospital environment. A critical review of the literature between 2011 and 2016 was undertaken. The following databases were searched: MedLine, CINAHL, AMED, Web of Science and ASSIA. Searches included words from three categories: cultural activities, outcomes and healthcare settings. Initial searches identified 131 potentially relevant articles. Following screening and review by the research team, a total of 69 studies were included in the final review. The majority of studies examined the effect of music listening on patients/service users (76.8%). These studies were primarily quantitative focusing on the measurable effects of music listening in a surgical context. Overall, the studies in the review support the growing evidence base on the value of the arts in a variety of healthcare settings for patients/service users. The review findings suggest that now is the time for different voices and art forms to be considered and represented in the research on arts in healthcare. Further research is also required to strengthen the existing evidence base.